SOCIAL INTERACTIONAS LIBRARIAN SOFT SKILL IN SOCIO COMMUNICATION PERSPECTIVE:LIBRARIAN AS COMMUNICATOR AND EDUCATOR IN USER EDUCATION - BAKHTIYAR (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The purpose of the study is to describe social interaction as a librarian's soft skill, the role of librarians as communicators and educators in user education. The research focuses on research based on activities based on comprehensive detailed analysis of the main content, namely the role of librarians as communicators and educators in user education. In order not to bias the topic of discussion, the research covers the analysis in the main study, namely social interaction as a librarian's soft skill. Analysis requires realistic critical thinking. Applying conceptualization in the historical range in the past or currently happening, it is appropriate to use the historical approach. His analysis utilizes the characteristic of critical inquiry to analyze the development of a thought. Primary sources of information are used as primary data. Historical approach data collection techniques empower library research, carry out reading activities of various literatures on the topic of soft skill conceptualization, social interaction, communication and the role of librarians as communicators and educators in user education, so that synchronization and harmonization occur. line of thought on various conceptualizations. The data were analyzed descriptively qualitatively, based on the sources of analysis of various reading materials, which were study or theoretical, research and not research. The validity of the study is realized by empowering content analysis, it is useful to analyze the various meanings of the most important conceptualizations. Observations were carried out to observe the various activities of the librarian's role being utilized as a supporting element in constructing theory. Research result; (a) librarians interact socially well if they are capable of possessing information competence from the results of education and experience, must be developed to be manifested in information skills in various situations and service conditions, (b) library programs can improve the ability of librarians as communicators and educators, namely educational users. (c) communication is the main element to support the existence of the library, because it ensures smooth coordination with various related parties.